IMPLEMENTASI LEAN HOSPITAL DI SUB. BAGIAN LOGISTIK RUMAH SAKIT IMMANUEL BANDUNG - Yuliani, Yuliani; Salsabila, Salsabila (Jurnal Sehat Masada, 2025)
Hospitals in Indonesia are currently facing challenges in improving operational efficiency and effectiveness. One of the quality improvement methods used is Lean Hospital, which aims to eliminate waste and improve the quality of service. This study aims to analyze the implementation of Lean Hospital in increasing the effectiveness and efficiency in the process of issuing goods in the logistics of Immanuel Hospital Bandung. The specific goal is to identify existing types of waste, analyze current workflows, and design more efficient workflows using Value Stream Mapping (VSM). This study uses a qualitative method with a descriptive approach. Data was collected through direct observation, interviews with logistics officers, and analysis of related documents. Current workflows are analyzed using VSM to identify existing types of waste, such as defects, motion, waiting, transportation, inventory, overproduction, and overprocessing. The results of the study were obtained waste defect, motion, waiting and overprocessing.